Level up: the expression of male sexually selected cuticular hydrocarbons is mediated by sexual experience. (February 2016) - Gershman, Susan N.; Rundle, Howard D.
Abstract : The use of cuticular hydrocarbons (CHCs) in species recognition, sex identification and sexual selection is widespread in insects. However, few studies have studied plasticity in CHCs. Here we examine the effect of age and social environment on a suite of sexually selected CHCs in Drosophila serrata . We demonstrate that the combination of CHCs that is associated with increased male mating success (CHCβ) changes as males age, and this effect is mediated by social environment. When single males were housed with multiple females, their expression of CHCβ increased across the first few days of their adult life, after which expression declined with increasing age. In contrast, sexually selected CHCs of males housed with other males, males housed with other males and females, and males housed alone all decreased across days. To determine the long-term consequences of mating on CHC expression, we allowed males a single mating opportunity and subsequently found some indication of a brief spike in CHCβ. Finally, to determine whether visual and olfactory contact with females, copulation, or intromission causes males to express high values of CHCβ, we manipulated male access and physical contact with females. We found that although prolonged copulation causes a slight increase in male CHCβ, only a successful copulation with sperm transfer induced males to develop CHCs associated with high mating success. Taken as a whole, our results demonstrate that the expression of sexually selected CHCs in males varies with both age and social context, and suggest that the latter is mediated at least in part by successful matings with females. More generally, contextual plasticity in CHCs is likely to affect both the experimental design of CHC-based experiments and the evolution of CHC signals as naturally and sexually selected traits. Highlights: We tracked changes in cuticular hydrocarbon (CHC) expression with age in male Drosophila serrata . CHCs associated with increased mating success (CHCβ) changed with male age. Age-specific effects on CHCβ were mediated by social environment. Males with greater access to females expressed higher CHCβ values. Mating, but not visual, olfactory or physical contact with females, altered CHCβ.